Risk assessment in submarine outfall projects: The case of Portugal - Mendonça, A. C. (2013)
Submarine outfalls need to be evaluated as part of an integrated environmental protection system for coastal areas. Although outfalls are tight with the diversity of economic activities along a densely populated coastline being effluent treatment and effluent reuse a sign of economic prosperity, precautions must be taken in the construction of these structures. They must be designed so as to have the least possible impact on the environment and at the same time be economically viable. This paper outlines the initial phases of a risk assessment procedure for submarine outfall projects. This approach includes a cost-benefit analysis in which risks are systematically minimized or eliminated. The methods used in this study also allow for randomness and uncertainty. The input for the analysis is a wide range of information and data concerning the failure probability of outfalls and the consequences of an operational stoppage or failure. As part of this risk assessment, target design levels of reliability, functionality, and operationality were defined for the outfalls. These levels were based on an inventory of risks associated with such construction projects, and thus afforded the possibility of identifying possible failure modes. This assessment procedure was then applied to four case studies in Portugal. The results obtained were the values concerning the useful life of the outfalls at the four sites and their joint probability of failure against the principal failure modes assigned to ultimate and serviceability limit states. Also defined were the minimum operationality of these outfalls, the average number of admissible technical breakdowns, and the maximum allowed duration of a stoppage mode. It was found that these values were in consonance with the nature of the effluent (tourist-related, industrial, or mixed) as well as its importance for the local economy. Even more important, this risk assessment procedure was able to measure the impact of the outfalls on human health and the environment.